2021
DOI: 10.1186/s12940-021-00793-0
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to second-hand smoke during early life and subsequent sleep problems in children: a population-based cross-sectional study

Abstract: Background Previous studies have revealed that current secondhand smoke exposure showed highly suggestive evidence for increased risk of simultaneous sleep problems in children. Data on the associations between early-life exposure to SHS with subsequent sleep problems in children were scarce. We aimed to evaluate the associations of early-life SHS exposure with sleep problems in children. Methods In this cross-sectional study, children were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The major finding that SHS exposure is significantly associated with poor sleep quality is consistent with findings from some previous studies in different population groups, including children 2 , 37 , adolescents 2 , 38 , university students 22 , and adults 6 , 31 . Although similar findings are widely reported in literature, a study in USA found no statistically significant relationship between poor sleep quality and SHS among the general population 39 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The major finding that SHS exposure is significantly associated with poor sleep quality is consistent with findings from some previous studies in different population groups, including children 2 , 37 , adolescents 2 , 38 , university students 22 , and adults 6 , 31 . Although similar findings are widely reported in literature, a study in USA found no statistically significant relationship between poor sleep quality and SHS among the general population 39 .…”
Section: Discussionsupporting
confidence: 91%
“…International studies exploring this relationship do exist. In China, for example, studies have reported a significant relationship between SHS exposure and sleep quality among young adults and children 2 , 30 . In Turkey, approximately two-thirds of adult students sampled from a university reported SHS exposure as one of the key contributors of poor sleep quality 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Sleep quality is a comprehensive sleep assessment indicator that includes sleep duration and other sleep manifestations. Although most studies focus on the sleep quality of healthy individuals 13,25,26 , there is still insufficient research on the relationship between SHS exposure and sleep quality in patients with chronic diseases. In this context, we observed that hypertensive males exposed to SHS had good sleep quality, which individual differences, lifestyle, and psychological factors may influence.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbance scale for children (SDSC) 30 , 31 is a recognized measurement: There are 34 items about sleep difficulties, breathing disorders, arousal disorders, conversion disorders, excessive somnolence and sweating at night, to assess the extent to which various factors interfere with the quality of sleep in patients. The score for each question is 5, and the total score ranges from 34 to 170.…”
Section: Methodsmentioning
confidence: 99%